Uncovering Global Research Patterns in Safety Risk Assessment: Insights from a Bibliometric Approach - Bastuti, Sofian; Mohammad, Roslina; Fatah, Abdul Yasser Abd; Alfatiyah, Rini (Journal of Ecohumanism, 2024)
Safety Risk Assessment (SRA) has attracted considerable attention from both practitioners and scholars over the past decade, driven primarily by the increasing frequency of workplace accidents and occupational diseases, particularly in developing countries. This recognition has led many organizations to prioritize SRA as a fundamental practice for mitigating workplace hazards and enhancing occupational safety. This study aims to elucidate global research patterns in SRA by analyzing the distribution of related publications from the perspectives of authorship, countries, institutions, and research trends. Utilizing a bibliometric analysis approach, data were retrieved from the Scopus database and analyzed using VOSviewer software. A comprehensive analysis of 1888 research articles published between 1970 and 2023 was conducted, focusing on international collaboration, keyword co-occurrence, and thematic trends to identify prevailing topics and emerging areas in SRA research. The results reveal a notable increase in SRA-related publications since 2006, with an accelerated growth observed post-2018. China and the United States are highlighted as leading contributors, with China demonstrating significant intra-country research dominance. The analysis also indicates that keywords such as ‘Safety Risk Assessment’ and ‘Food Safety’ are frequently emphasized, underscoring core research interests in the identification and management of safety risks. Furthermore, the integration of advanced technologies, including the Internet of Things (IoT) and big data, represents a growing trend in the field. This study provides valuable insights into the current state and evolution of SRA research, serving as a foundational reference for future scholarly exploration and practical implementation.